Regional frequency analysis of stream temperature at ungauged sites using non-linear canonical correlation analysis and generalized additive models. (May 2023) - Souaissi, Zina; Ouarda, Taha B.M.J.; St-Hilaire, André; Ouali, Dhouha
Highlights: Improve the estimation of water temperature extremes at ungauged sites. Incorporate non-linearities in the homogenous region delineation step using NLCCA. Consider non-linear models in the whole estimation procedure (NLCCA + GAM). Compare fully and partially non-linear approaches for water temperature regionalization. The results underline the importance of considering the non-linearity of thermal processes.